# Simplify (x-2)^2

Luca B. | Certified Educator

calendarEducator since 2011

starTop subjects are Math, Science, and Business

You need to expand the binomial using the formula `(a-b)^2 = a^2 - 2ab + b^2` .

Hence, substituting x for a and 2 for b yields:

`(x - 2)^2 = x^2 - 4x + 4`

You may also use distributive multiplication such that:

`(x - 2)^2 = (x - 2)(x - 2) = (x-2)*x +(x-2)*(-2)`

Opening the brackets yields:

`(x - 2)^2 = x*x - 2*x + x*(-2) - 2*(-2)`

`(x - 2)^2 = x^2 - 2x - 2x + 4`

`(x - 2)^2 = x^2 - 4x + 4`

Hence, expanding the binomial `(x-2)^2`  yields `(x - 2)^2 = x^2 - 4x + 4.`

check Approved by eNotes Editorial

johnynickelson | Student

I solved that kind of problem when i was in school.(x-2)^2 is a simple quadratic equation and it can be solve by using (a-b)^2 formula.green cookware

winsorburnell | Student

It's simple quadratic equationYou can used the formula of (a-b) the whole square.you have to just factorized the equation.luxury vacation bali

scorpio37 | Student

(x-2)^2=(x-2)(x-2)